2001
DOI: 10.1538/expanim.50.67
|View full text |Cite
|
Sign up to set email alerts
|

Lack of B Cell Leakiness in BALB/cA-nu, scid Double Mutant Mice.

Abstract: BALB/cA mice homozygous for both nu and scid mutations (BALB/cA-nu/nu, scid/scid) were developed by mating between BALB/cA-scid and BALB/cA-nu. These mice have greater longevity than C.B-17-scid because no thymic lymphoma occurs in them unlike in the latter. C.B-17-scid is known to show the leaky phenomenon in which a few clones of functional T and B cells develop in aged C.B-17-scid. Unexpectedly, the leaky B cells and T cells were absent or suppressed in BALB/cA-nu, scid mice when cytokine expressions were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…1, Igs (IgG + IgM) at concentrations ranging between 1 and 10 µg/ml were detected in 15 (30 %) of 50 NOD-scid mice. These Ig levels were not considered representative of leakiness as they fell below the 10 µg/ml of serum Ig levels that define the leaky phenotype [5]. However, 121 of the NOG mice tested in the present study did not show detectable Igs.…”
mentioning
confidence: 61%
See 2 more Smart Citations
“…1, Igs (IgG + IgM) at concentrations ranging between 1 and 10 µg/ml were detected in 15 (30 %) of 50 NOD-scid mice. These Ig levels were not considered representative of leakiness as they fell below the 10 µg/ml of serum Ig levels that define the leaky phenotype [5]. However, 121 of the NOG mice tested in the present study did not show detectable Igs.…”
mentioning
confidence: 61%
“…A previous study by our group showed the absence of Ig production and T cell leakiness in BALB/cA-scid, nu mice [5]. The absence of leaky cells in these mice may be due to the lack of T cell development in the absence of a thymus.…”
mentioning
confidence: 64%
See 1 more Smart Citation
“…It has been reported that such leakiness is higher in mice housed under nonspecific pathogen-free conditions, which is the type of facility in which we house our mice, and leakiness is generally higher on the C57BL/6 genetic background. [38][39][40] The FVIII null mice crossed with NSG mice were on a mixed genetic background of C57BL/6 and 129/SV, so NSGF8KO mice inherited a mixed genetic background of C57BL/6, 129/SV, and NOD. Backcrossing NSGF8KO mice to a pure NOD background will need to be pursued in future studies.…”
Section: Human Thrombocytopoiesis In the 2bf8lv Genetically Modified mentioning
confidence: 99%
“…The native condition of human mucosal tissue was attenuated by this phenomenon. Tsukinoki et al [27] established a transplantation technique for normal human oral mucosa that does not exhibit cystic changes using immunodeficient nu/scid mice, which were derived from a cross of nu/nu mice and scid/scid mice [9, 26]. However, the transplantation of gingival tissue from periodontal diseases has yet to be established in common immunodeficient nu/nu or scid/scid mice.…”
Section: Introductionmentioning
confidence: 99%